Experimental models for developing oncolytic virotherapy for metastatic prostate cancer - Chen, Ying-Cheng; Figueiredo, Marxa Leão (Frontiers in Immunology, 2025)
Cancer has remained the second leading cause of death worldwide for over a century. Despite significant advances, effectively targeting cancer cells and overcoming therapeutic challenges remain critical goals. In this review, we focus on advanced metastatic prostate tumors, where the patients’ five-year survival rate is less than 35%. While standard androgen deprivation therapy (ADT) has been effective for most prostate cancer patients, recurrence of aggressive tumors is common, emphasizing an urgent need for new treatment strategies. Immunotherapy has gained attention for its potential to harness the immune system against cancer cells. Among these, oncolytic virotherapy stands out for its tumor-specific tropism, its ability to transform or convert the immune-suppressive tumor microenvironment by enhancing immune cell infiltration, and its capacity for therapeutic gene delivery. This review explores the background of commonly used viruses, evaluation models (including cell culture, animal models, ex vivo platforms, and clinical trials), and the anticipated outcomes and challenges of oncolytic virotherapy. By addressing these aspects, we aim to provide a comprehensive overview of the current state and future directions of oncolytic virotherapy models in the treatment of advanced prostate cancer.